SPECIFIC FEATURES OF QUALITY MANAGEMENT IN TOURISM - Yusupova Meroj Nizamovna; Rakhimov Muzaffarbek Ibragimdzhanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article provides a theoretical overview of the specific features of quality management in the tourism sector. In addition, the specific features of tourist services and their content, the processes of quality management of services in the tourism sector, and a five-dimensional service dimension structure that focuses on customers are developed.